2008
DOI: 10.1021/jp802734a
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation of Second and Farther Hydration Shells of Alkali Cations and Bromide in Concentrated Aqueous Protein as a Water-Shortage Medium

Abstract: The Gibbs free energies of transfer of selected ions from water to concentrated aqueous ovalbumin and albumin (DeltaW(W') G degrees j) have been determined by ion-transfer voltammetry. Negative values for the tetrabutylammonium ion suggest its direct binding to ovalbumin. In contrast, for alkali cations and bromide, the DeltaW(W') G degrees j values are positive and increase with increasing ovalbumin concentration. Positive values are confirmed for concentrated aqueous albumin and poly(styrenesulfonate) as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Recently, Ohki et al estimated the contribution from the second or farther hydration shell to the entire hydration energies of alkali cations and bromide ion by ion-transfer voltammetry and XAFS. 66 According to this study, the contribution from the second or farther shells is larger than 10 -15 kJ mol -1 , corresponding to the energy of a single hydration bond formation. In addition, the energy of the perturbation becomes larger for smaller alkali cations.…”
Section: Ion Recognition Selectivitymentioning
confidence: 63%
“…Recently, Ohki et al estimated the contribution from the second or farther hydration shell to the entire hydration energies of alkali cations and bromide ion by ion-transfer voltammetry and XAFS. 66 According to this study, the contribution from the second or farther shells is larger than 10 -15 kJ mol -1 , corresponding to the energy of a single hydration bond formation. In addition, the energy of the perturbation becomes larger for smaller alkali cations.…”
Section: Ion Recognition Selectivitymentioning
confidence: 63%
“…There is evidence accumulating that ion association in surfactants and polyelectrolytes is accompanied by partial dehydration of counter-ions. [6][7][8][9] However, it is not clear whether this is the driving force for or a consequence of such interactions. Distinguishing between these is important for developing more realistic models of counter-ion binding.Theoretical treatment of interaction of metal ions with polyelectrolytes dates back over 60 years, 10-13 and although, ''binding'' is frequently used to include all interactions between charged polymers and metal cations, we will follow Manning 13 and use it to describe only the step where metal ions associate with polyelectrolytes.…”
mentioning
confidence: 99%
“…There is evidence accumulating that ion association in surfactants and polyelectrolytes is accompanied by partial dehydration of counter-ions. [6][7][8][9] However, it is not clear whether this is the driving force for or a consequence of such interactions. Distinguishing between these is important for developing more realistic models of counter-ion binding.…”
mentioning
confidence: 99%
“…Another interaction (reaction) energy descriptor is given with total energies of reactants and products obtained by first-principles DFT calculations energy as follows [14]: 6 ] is the total energy of the cationic water cluster. Although (2) does not provide information about local ion-dipole interaction such as the electrostatic approach in (1), but by ignoring inter-neighbour water interactions, we may obtain an average value for binding energy between the water molecules and the metal ion. A more convenient index which is comparable with the experimental hydration enthalpy per water molecule can be written as [16]:…”
Section: Methodsmentioning
confidence: 99%
“…The dehydration has been acknowledged as an essential molecular interaction for water-ion exchange reaction, since some experimental evidences have shown that ion attack at surfactants and polyelectrolyte is followed by its partial interaction of the counter-ions [1,2]. A recent study on counter ion-binding (aqueous Al(III) and Cr(III)) related to the ion attack at electrolyte polyvinyl sulphate (PVS) has brought up that hydration enthalpy from coordinated water release within the primary hydration sphere plays a key role in driving binding to PVS [3].…”
Section: Introductionmentioning
confidence: 99%